2007
DOI: 10.4321/s0365-66912007000600006
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de iris fláccido por tamsulosina: Estudio prospectivo frente a grupo control

Abstract: Intraoperative floppy-iris syndrome occurred in 67% of the patients treated with tamsulosin. The only postoperative secondary effect was a lower pupil reactivity in patients taking tamsulosin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…We found significantly less preoperative dilation in the tamsulosin-treated group, and the change in dynamic pupil area from the start of the operation to the end was also significantly greater. This was also reported by Bidaguren et al (2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found significantly less preoperative dilation in the tamsulosin-treated group, and the change in dynamic pupil area from the start of the operation to the end was also significantly greater. This was also reported by Bidaguren et al (2007).…”
Section: Discussionsupporting
confidence: 82%
“…We observed that patients on tamsulosin suffered a 12% decrease in central corneal endothelial cells compared with a 3% decrease in control subjects. A previous study by Bidaguren et al (2007) reported a loss of endothelial cells of 24% in a tamsulosin-treated group of male patients compared with a cell loss of 13% in the control group 1 month after cataract surgery. However, this difference in endothelial cell loss did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 86%
“…Along these lines, patients who are taking tamsulosin could encounter a risk of IFIS during cataract medical procedures. [ 4 24 25 ] The chronic use of tamsulosin promotes atrophy of the macular plate and subsequent pupil expansion; this could explain the flaccid nature of this tissue discovered during cataract medical procedures. [ 26 ] Pärssinen et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the retrospective study comparing the risk of IFIS between patients taking tamsulosin versus alfuzosin based on medical charts, major complications were observed in 15% of the patients with IFIS and included iris laceration, focal iris stromal atrophy, iris dialysis, iris hemorrhage, posterior capsular tear with vitreous loss, zonular dehiscence, transient postoperative hypertension, major iris trauma, and postoperative cystoid macular edema [21]. A prospective study detected higher tendency towards post-operative miosis in patients under treatment with tamsulosin than in the patients in the control group [29]. …”
mentioning
confidence: 99%
“…All patients underwent cataract surgery and were observed for IFIS features. IFIS did not occur in the control group; however, in the tamsulosin group, 67% of patients had one or more signs of IFIS [29]. …”
mentioning
confidence: 99%